Two dimensional echocardiography as an evidence for clinically significant murmur - N., Mohan Kumar; Patil, Vinutha; P., Varshini; M., Chaitra K. (International Journal of Contemporary Pediatrics, 2022)
Background: Heart murmurs are extra and abnormal sounds made by turbulent flow of blood through heart. The most common cardiac abnormality found on auscultation is murmur. Edler is regarded as father of echocardiography. This is based on reflection of sound waves by heart structures similar to the radio detection and ranging (RADAR) and sound navigation and ranging (SONAR). Methods: Our study was done in PICU of Kempegowda Institute of Medical Sciences hospital, Bangalore. Duration of study was 6 years that is from January 2015 to January 2020. During this period total 2304 pediatric cases with various diseases were admitted. Of these 150 (6.5%) children were having clinically significant murmur. All children who fulfilled inclusion criteria were subjected to 2d echo by GE VIVID portable 2 dimensional and colour Doppler echocardiography trans-thoracically. Results: 96 (64%) children had abnormal 2d echo. Of these 37 (38.5%) children were found to have organic heart disease and 59 (61.5%) had functional heart disease. Of these 37 children 10 (27%) had pulmonary arterial hypertension (PAH), 8 (21%) children had atrial septal defect, 7 (18%) had perforated foramen ovale (PFO), 2 (5%) had mitral valve prolapse, 2 (5%) had ventricular septal defect (VSD), 1(2%) had tetralogy of fallot (TOF), 1 (2%) had septal aneurysm, and 1 (2%) had pericardial effusion. Conclusions: There is 64% chances of detecting a heart disease, if 2D echo is done in children with clinically significant cardiac murmur. Hence 2D echo is a vital investigation in evaluating heart murmurs.